The effect of the Place mat strategy on the mathematical interconnection skills among middle school students - Al-Shammari, Maysam Maan Zaki; Risen, Hassan Kamil (Al-Adab Journal, 2022)
The aim of the research is to find out the effect of the place mat strategy on mathematical interconnection skills among middle school students, and to achieve the research goal, the researchers chose the two divisions represented by (B, D) from (Al-Idrisi Intermediate School for Boys) affiliated to the Directorate of Education Baghdad/ Karkh II for the academic year (2019/2020) (B) represents the experimental group and included (30) students who studied according to the place mat strategy, and (D) represents the control group and included (30) students who studied in the usual way, and the two groups (experimental and control) were rewarded in variables in terms of (chronological age) Previous collection for (2018/2019), Riyadh knowledge test The previous one, intelligence test, mathematical correlation skills test) and both researchers built the research tool represented by mathematical correlation skills testing in mathematics and included (28) substantive paragraphs (multiple choice), and its validity, reliability and psychometric properties were verified and the results were analyzed using statistical means and after The end of the experiment period The research tool was applied to the two groups, and the treatment results resulted in the superiority of the experimental group students over the control group students in the mathematical correlation skills test.